Crime of Sexual Abuse of Children in Turkish Penal Code Five Case Reports - Fırat, Sunay; İltaş, Yiğit and Gülmen, Mete Korkut (The Bulletin of Legal Medicine, 2017)
Sexual abuse of children is a very important health problem; moreover, it is regarded as a serious crime in terms of psycho-social and legal aspects when it is dealt with possible reasons to appear in the short and long term. Protection of children is especially given much importance for crimes of sexual privacy all over the world. In this study, it is aimed to protect children who are victims of this crime and to prevent this crime through the cases brought to Adana Heavy Penal Court with regard to crimes against the right of sexual privacy of children which is subject to sanctions in Turkish Penal Code. Data belonging to their offenders and 5 victim children under 15 who have been brought/sent/have applied to 3 Numbered Heavy Penal Court of Adana Court House after January 2010 because of abuse of children and child neglect have been investigated retrospectively. When our cases are evaluated, it is understood that one girl at the age of 13 years 11 months has been pushed to prostitution out of 5 cases. It is learned that 4 victim children of our cases at the age of 12 years 3 months, 12 years 10 months, 13 years 9 months and 14 years 7 months have been forecd to marry illegally, brought to hospital due to illness after giving birth and/or for giving birth and concerning health officials filed a criminal complaint to the security office and legal process started for them. Abuse of children can happen in any place of the world, and it is understood that it is so common when you deal with the case. As the number of professionals and their sensitivity and their knowledge increases, concerning numbers generally increase too. As it can be seen, medicine, law and social service departments must work cooperatively for the evaluation of abuse of children. Remedying the deficiencies for this point will be a significant development for our country. As a result, it is a requirement for our country that necessary coordination and cooperation between concerning institutions should be provided for prevention of child neglect and abuse of children.